Investigation of aerodynamic parameters of a hybrid airship - Andan, Amelda Dianne; Asrar, Waqar; Omar, Ashraf Ali (American Institute of Aeronautical and Astronautic, 2012)
The aerodynamic parameters of a preliminary winged-hull airship design are investigated. The research methodology involved the use of numerical simulation and wind tunnel testing. The aerodynamic parameters of the design are first computed using a commercial CFD code. The force and moment coefficients are then measured on a scaled model in the IIUM low speed wind tunnel. The experimental results generally agree with the CFD predicted data. Addition of a wing to conventional airship increases the lift substantially with a reasonable increase in drag. The longitudinal and directional stabilities were found to be statically stable, however, both the conventional airship and the hybrid airship were found to have poor rolling stability. CFD simulations show that modifications to the wing placement and its dihedral have strong positive effect on the rolling stability.